Homozygosity in any HLA locus is a risk factor for specific antibody production: the taboo concept 2.0 - Loeffler-Wirth, Henry; Lehmann, Claudia; Lachmann, Nils; Doxiadis, Ilias (Frontiers in Immunology, 2024)
Objective: In a cooperative study of the University Hospital Leipzig, University of Leipzig, and the Charité Berlin on kidney transplant patients, we analysed the occurrence of HLA specific antibodies with respect to the HLA set up of the patients. We aimed at the definition of specific HLA antigens towards which the patients produced these antibodies. Methods: Patients were typed for the relevant HLA determinants using mainly the next generation technology. Antibody screening was performed by the state-of-the-art multiplex-based technology using microspheres coupled with the respective HLA alleles of HLA-Class I, and II determinants. Results: Patients homozygous for: HLA-B*A02, HLA-A*03, HLA-A*24, HLA-B*07, HLA-B*18, HLA-B*35, HLA-B*44, HLA-C*03, HLA-C*04, HLA-C*07 in the class I group and for the class II group: HLA-DRB1*01, HLA-DRB1*03, HLA-DRB1*07, HLA-DRB1*15, HLA-DQA1*01, HLA-DQA1*05, HLA-DQB1*02, HLA-DQB1*03( 7), HLA-DQB1*06, HLA-DPA1*01, and HLA-DPB1*04 were found to have a significant higher antibody production compared to the heterozygous ones. In general, all HLA determinants are affected. Remarkably, HLA-A*24 homozygous patients can produce antibodies towards all HLA-A determinants, while HLA-B*18 homozygous ones make antibodies towards all HLA-B and selected HLA-A and C antigens, and are associated with an elevation of HLA-DRB1 parts of DQB1, and DPB1 alleles. Homozygosity for the HLA class II HLA-DRB1*01, and HLA-DRB1*15 seems to increase the risk for antibody responses against most of the HLA class I antigens (HLA-A, B and C) in contrast to HLA-DQB1*03( 7) where a lower risk towards few HLA-A and -B alleles is found. The widely observed differential antibody response is therefore to be accounted to the patient's HLA type.Homozygous patients are at risk to produce HLA specific antibodies hampering the outcome of transplantation. Including this information on the allocation procedure might reduce antibody mediated immune reactivity and prevent graft loss in the patient at risk increasing the life span of the transplanted organ.